A silver metal complex as a luminescent probe for enzymatic sensing of glucose in blood plasma and urine. Issue 25 (13th June 2018) - Pan, Zheng-Bang; Wang, Ying-Chu; Chakkaradhari, Gomathy; Zhu, Jian Fan; He, Rong-Yu; Liu, Yu-Ci; Hsu, Chia-Hui; Koshevoy, Igor O.; Chou, Pi-Tai; Pan, Sheng-Wei; Ho, Mei-Lin
Abstract : In this work, we present a facile preparation of a paper-based glucose assay for rapid, sensitive, and quantitative measurement of glucose in blood plasma and urine. Abstract : In this work, we present a facile preparation of a paper-based glucose assay for rapid, sensitive, and quantitative measurement of glucose in blood plasma and urine. Two copper phosphorescent complexes [Cu(2, 9-dimethyl-4, 7-diphenyl-1, 10-phenanthroline)(2, 6-dimethylphenylisocyanide)2 ][B(C6 H3 (CF3 )2 )4 ] (Cu1 ) and [Cu(2, 9-dimethyl-1, 10-phenanthroline)(2, 6-dimethylphenylisocyanide)2 ][B(C6 H3 (CF3 )2 )4 ] (Cu2 ) and a new silver congener [Ag(P 3 )CNAg(P 3 )][B(C6 H3 (CF3 )2 )4 ] (Ag3 ) (P 3 = PPh2 C6 H4 -PPh-C6 H4 PPh2 [bis( o -diphenylphosphinophenyl)phenylphosphine]) have been synthesized and their oxygen sensing abilities were investigated. The dimetallic phosphine-basedAg3 complex, having a high oxygen sensing ability, was employed as an efficient signal transducer in enzymatic reactions to recognize blood plasma glucose and urine glucose, which provided a wide linear response for a concentration range between 1.0 and 35 mM and a rapid response, with a limit of detection (LOD) of 0.09 mM for glucose. In practical application, thisAg3 paper-based device offers great analytical reliability and accuracy upon monitoring glucose concentrations in blood plasma.